Hidrólise de polissacarídeos de biomassa microalgal biofloculada com fungo - Simon, Viviane (2023)
The microalgae Spirulina platensis is a microorganism with great application potential biotechnology. Among the obstacles associated with the cultivation process, the harvest of biomass. Bioflocculation is a viable alternative, as it uses microbial biomass, such as Aspergillus niger, as bioflocculants. The biomass resulting from the Bioflocculation can be used to produce high-value-added bioproducts. For the Cell disruption methods are used to fully exploit this biomass. Therefore, it is Specific knowledge of microbial composition and cellular structure is important for ensure the efficiency of hydrolysis and conversion into bioproducts. For cell rupture they are very physical-chemical or biological treatments (use of microorganisms or enzymes) are used. Given the specificity of enzymes, enzymatic hydrolysis is advantageous compared to commonly used technologies, and it is important to know which enzymes are necessary for the hydrolysis of each type of biomass. Furthermore, it is known that enzymes existing commercial products are applicable, but are not developed especially for the hydrolysis of plant biomass, requiring knowledge of how they act in microbial biomasses in relation to operational ranges of use. In this sense, the objective of study is to evaluate physical and enzymatic processes in the hydrolysis of microbial biomasses to application in energy production. Initially, microalgal harvesting tests were carried out with different bioflocculant contents and millivoltage adjustment for the microalgae S. platensis, achieving efficiencies of 99.7% (1:8 fungus:microalgae ratio). With an increase in scale the efficiency results were maintained. For bioflocculated biomass were tested, subsequently, pre-treatments (ultrasound, autoclave and freezing/thawing), which were evaluated based on the release of total reducing sugars (AR) over 6 h, pH 4.5, 50 ºC, 120 rpm in a water bath, with the addition of amylase enzymes (Amylase AG XXL), AMG (Sazyme GO2 e), cellulase (Celuclast 1.5 L) and xylanase (Ultraflo Max). From the best efficiency results, were defined as standard pretreatment, autoclaving. In then, the characterization of the enzymes was carried out in relation to pH and ideal temperatures, using your standard substrates. At this stage, another amylase enzyme was added (LpHera) to the tests. All enzymes had greater activity at pH 4.5 and temperatures 60º (Amylase and AMG), 70ºC (cellulase) and 50 ºC (xylanase). With optimal temperatures and pHs defined, enzyme addition percentages (0.01, 0.03 and 0.05%) were tested for hydrolysis of bioflocculated biomass. The tests were carried out until stabilization in the yields of AIR. In general, there was no statistical difference between enzyme concentrations used, with the use being defined as 0.01%. Next, different associations were tested of enzymes in the hydrolysis of bioflocculated biomass, and the use of Blend containing amylase, AMG and cellulase obtained the best results, with approximately 70% efficiency, considering pre-treatment and enzymatic action. The associated use of enzymes proved to be more efficient than individual use, being an alternative to the hydrolysis of biomass complex, such as the bioflocculated one that contains A. niger. Furthermore, the importance of optimization in enzymatic hydrolysis processes, and depending on the biomass used, enzymes can act in different ways, requiring concentration studies, operating time and associated use, mainly.